Arx Polyalanine Expansion in Mice Leads to Reduced Pancreatic α-Cell Specification and Increased α-Cell Death - Wilcox, Crystal L.; Terry, Natalie A.; May, Catherine Lee (PLOS ONE, 2013)
ARX/Arx is a homeodomain-containing transcription factor necessary for the specification and early maintenance of pancreatic endocrine α-cells. Many transcription factors important to pancreas development, including ARX/Arx, are also crucial for proper brain development. Although null mutations of ARX in human patients result in the severe neurologic syndrome XLAG (X-linked lissencephaly associated with abnormal genitalia), the most common mutation is the expansion of the first polyalanine tract of ARX, which results primarily in the clinical syndrome ISSX (infantile spasms). Mouse models of XLAG, ISSX and other human ARX mutations demonstrate a direct genotype-phenotype correlation in ARX-related neurologic disorders. Furthermore, mouse models utilizing a polyalanine tract expansion mutation have illustrated critical developmental differences between null mutations and expansion mutations in the brain, revealing context-specific defects. Although Arx is known to be required for the specification and early maintenance of pancreatic glucagon-producing α-cells, the consequences of the Arx polyalanine expansion on pancreas development remain unknown. Here we report that mice with an expansion mutation in the first polyalanine tract of Arx exhibit impaired α-cell specification and maintenance, with gradual α-cell loss due to apoptosis. This is in contrast to the re-specification of α-cells into β- and δ-cells that occurs in mice null for Arx. Overall, our analysis of an Arx polyalanine expansion mutation on pancreatic development suggests that impaired α-cell function might also occur in ISSX patients.